Kualitas Telur Ayam Ras Setelah Pemberian Olesan Lidah Buaya ( Aloe vera) dan Lama Penyimpanan Waktu yang Berbeda - Purwaningsih, Dewi; Djaelani, Muhammad Anwar; Saraswati, Tyas Rini (BULETIN ANATOMI DAN FISIOLOGI dh SELLULA, 2016)
Egg quality needs to be maintained so that the chemicals contained in eggs can be maintained freshness. The purpose of this study was to determine whether administration of a smear by using natural ingredients Aloe vera can maintain the quality of eggs. A total of 35 eggs used in this study. The samples were divided into 7 treatment groups, each treatment was repeated 5 times. P0 (1 day old egg without a smear of Aloe vera), P1 (6 days old egg without a smear of Aloe vera), P2 (12 days days old egg without a smear of Aloe vera), P3 (24 days old egg without a smear of Aloe vera), P4 (6 days old egg with a smear of Aloe vera), P5 (12 days days old egg with a smear of Aloe vera) and P6 (24 days old egg with a smear of Aloe vera). The study was conducted by measuring pH, Haugh unit, yolk index and egg weight as variable quality of the eggs. Data were analyzed using ANOVA, followed by a further test using Duncan test. The results showed that both egg storage time smeared Aloe vera and Aloe vera are not smeared both degrade the quality of chicken eggs, but by giving a smear of Aloe vera are still able to maintain for 6 days.   Keywords: Aloe vera, chemical contens, egg’s quality, chiken egg’s